2018
DOI: 10.1002/jclp.22629
|View full text |Cite
|
Sign up to set email alerts
|

Validating an abbreviated version of the Obsessive Beliefs Questionnaire

Abstract: The OBQ-9 appears to be a psychometrically sound tool for routine outcome monitoring of dysfunctional beliefs in hospital-based settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…To examine whether the IU questionnaires reflect the IU concept, previous articles compared the seven IU questionnaires with relevant clinical variables, such as worry, anxiety, OCD, and depression (Carleton et al, 2007; Cowie et al, 2018; Huntley et al, 2020; Moulding et al, 2011; Osmanağaoğlu et al, 2021; Rifkin & Kendall, 2020). Several articles also investigated the associations between these IU measures and other cognitive, emotional, and behavioral variables, such as metacognitive beliefs, anxiety sensitivity, fear and obsessive behaviors, and personality variables (Bredemeier et al, 2019; Gagné et al, 2018; Hong & Lee, 2015; Khawaja & Yu, 2010; Nagel et al, 2023; Rodgers et al, 2016; Wilson et al, 2020). Although different articles used different instruments to test the convergent validity of the IU questionnaires, the associations found suggest reasonable convergent validity.…”
Section: Discussionmentioning
confidence: 99%
“…To examine whether the IU questionnaires reflect the IU concept, previous articles compared the seven IU questionnaires with relevant clinical variables, such as worry, anxiety, OCD, and depression (Carleton et al, 2007; Cowie et al, 2018; Huntley et al, 2020; Moulding et al, 2011; Osmanağaoğlu et al, 2021; Rifkin & Kendall, 2020). Several articles also investigated the associations between these IU measures and other cognitive, emotional, and behavioral variables, such as metacognitive beliefs, anxiety sensitivity, fear and obsessive behaviors, and personality variables (Bredemeier et al, 2019; Gagné et al, 2018; Hong & Lee, 2015; Khawaja & Yu, 2010; Nagel et al, 2023; Rodgers et al, 2016; Wilson et al, 2020). Although different articles used different instruments to test the convergent validity of the IU questionnaires, the associations found suggest reasonable convergent validity.…”
Section: Discussionmentioning
confidence: 99%
“…Their body weight (kg) and height (cm) were self-reported. To evaluate the convergent validity of TON-17, the Eating Attitudes Test Short-Form (EAT-26) [ 29 , 30 ] and the Obsessive Beliefs Questionnaire Short-Form-9 (OBQ-9) [ 31 , 32 ] were used. The eating behaviors of the participants were evaluated with EAT-26, and obsessive disorders were evaluated with OBQ-9.…”
Section: Methodsmentioning
confidence: 99%
“…Their body weight (kg) and height (cm) were based on their self-report. The Eating Attitudes Test-Short Form (EAT-26) was used to evaluate the participants' eating behaviors [35,36], and the Obsessive Beliefs Questionnaire-Short Form 9 (OBQ-9) to evaluate their existing obsessive disorders [37,38].…”
Section: Design and Proceduresmentioning
confidence: 99%
“…The Obsessive Beliefs Questionnaire (OBQ), which was developed by an international working group to evaluate cognitive biases speci c to obsessive compulsive disorder and consisted of 87 items in its initial version, was later used as OBQ-44 with 44 items [40,41]. Gagné et al [37] Both the total score and the 3 sub-dimension scores of the scale can be used separately [38]. In this study, the Cronbach's α was found to be 0.762 for the total OBQ-9.…”
Section: Eating Attitudes Test-short Form (Eat-26)mentioning
confidence: 99%